2014
DOI: 10.1111/adj.12210
|View full text |Cite
|
Sign up to set email alerts
|

Rubber dam application in endodontic practice: an update on critical educational and ethical dilemmas

Abstract: Proper isolation is an essential prerequisite for successful endodontic treatment. This article aims to provide an update on the prevalence of rubber dam (RD) use, and the role of education along with attitudes of general dental practitioners (GDPs) and patients towards the application of RD in endodontics. Critical ethical issues are also highlighted. Using certain keywords, an electronic search was conducted spanning the period from January 1983 to April 2013 to identify the available related investigations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 39 publications
1
32
1
6
Order By: Relevance
“…Based on the fact that the clinical pathway of hospital information management has been included in the treatment of chronic pulpitis of deciduous teeth, the theme of QCC activity is to increase the usage of rubber dam in root canal treatment of chronic pulpitis of deciduous teeth. Rubber dam in root canal treatment has been recognized as a standard treatment procedure internationally [10]. In developed countries, rubber dams have been widely used in children's oral treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the fact that the clinical pathway of hospital information management has been included in the treatment of chronic pulpitis of deciduous teeth, the theme of QCC activity is to increase the usage of rubber dam in root canal treatment of chronic pulpitis of deciduous teeth. Rubber dam in root canal treatment has been recognized as a standard treatment procedure internationally [10]. In developed countries, rubber dams have been widely used in children's oral treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A recent literature review concluded that rubber dam use is also the international standard. 12 Technically, the standard of care in the USA is decided by the legal system on a case-by-case basis. 13–15 However, courts usually rely on a professional consensus about what a reasonable dentist would do in a similar circumstance.…”
Section: Introductionmentioning
confidence: 99%
“…The use of apex locator in this case was beneficial to minimize additional radiographic exposures, and potential gagging reflexes (1,14). In addition, determining the exact location of the minor diameter of the apical foramen was of prime importance to prevent potential mechanical irritation of the periapical area since the inferior alveolar canal lies between the mesial roots apices.…”
Section: Discussionmentioning
confidence: 95%
“…Despite the fact that the rubber dam is generally tolerated by patients, clinicians may face some difficulties while placing the rubber dam assembly on a mandibular third molar (1,14) That's why caution should be given to keep the rubber dam away from gagging reflex trigger areas (1,14). The use of apex locator in this case was beneficial to minimize additional radiographic exposures, and potential gagging reflexes (1,14).…”
Section: Discussionmentioning
confidence: 95%